Expanding binge eating assessment: Validity and screening value of the Binge Eating Scale in women from the general population - Duarte, Cristiana (2015)
There is growing recognition that binge eating is a prevalent problem with serious implications for both clinical and nonclinical samples. The current study aimed at examining the factor structure, psychometric properties and the screening usefulness of the Binge Eating Scale (BES) in a large sample of female college students and women from the Portuguese general population. A sample of 1008 participants was collected to conduct a confirmatory factor analysis and test the BES psychometric properties; 150 participants were further evaluated through the Eating Disorder Examination 16.0D to assess the discriminant validity of the BES. Results confirmed that the BES presents a sound one-dimensional factorial structure, with very good construct reliability and convergent validity. Also, the scale presented very good retest-reliability. Findings also offered evidence that the BES is positively associated with measures of eating and general psychopathology, and BMI. Furthermore, the BES revealed an excellent performance (96.7%) on discriminating clinically significant cases of binge eating, showing a sensitivity of 81.8% and a specificity of 97.8%. Results support the validity and usefulness of the BES as an assessment and screening tool for binge eating in women from the general population.